CONFISCATION ON STATE-OWNED ENTERPRISES (BUMN) ASSETS IN THE PERSPECTIVE OF TAXATION LAW - Zainal Muttaqin (Faculty of Law, Universitas Jenderal Soedirman, 2018)
Regime of the State Finance Law as stipulated in Law Number 17 Year 2003 and Law Number 1 Year 2004 classify separated state finances as State-owned enterprises (BUMN) capital into the definition of state finances of which assets are free from confiscation. The problem is in terms that BUMN as taxpayers do not pay the tax debt, thus is it possible for BUMN to be enforced by law in the form of confiscation of its wealth? This paper aims to analyze the above issues based on applicable legal doctrine. From a legal perspective, State-owned enterprises is a separate legal entity from the owner of capital (state). Thus, the capital sourced from the state in the State-owned enterprises is not the property of the state anymore yet a wealth of state enterprises as legal entities as well as taxpayers. As a result, Law Number 17 Year 2003 which explained that state assets separated in BUMN including state assets is inconsistent with applicable legal theory. Accordingly, Article 50 paragraph (1) of Law Number 1 Year 2004 should have not been applied to State-owned enterprises.Keywords: BUMN, Confiscation, Legal Entity, State Finance, Tax.